Electrochemical Oxidation of Hazardous Tetracene to Highly Redox Active Anthraquinone and Hydroquinone Derivatives on a Carbon Nanotube‐Modified Electrode and Its Selective Hydrogen Peroxide Sensing. Issue 11 (12th August 2014) - Barathi, Palani; Kumar, Annamalai Senthil; Aggarwal, Suresh K.
Abstract A simple method for electrochemical oxidation and degradation of carcinogenic tetracene (TC) to surface confined redox active quinone species (TCO) on a pristine‐multiwalled carbon nanotube modified (MWCNT) gold electrode surface (Au/MWCNT) by applying a static potential at 0.9 V vs. Ag/AgCl in pH 7 phosphate buffer solution has been demonstrated. Various physicochemical characterizations of MWCNT@TCO by TEM, FT‐IR, Raman spectroscopy and GC‐MS reveal the presence of two types of redox sites, hydroquinone and anthraquinone derivatives within the MWCNT@TCO. The modified electrode showed selective electrocatalytic reduction and amperometric i–t sensing of H2O2 with a detection limit (signal‐to‐noise=3) of 122 nM.